On the S-matrix of type 0 string theory - DeWolfe, Oliver; Walcher, Johannes (Arxiv, 2003)
The recent discovery of non-perturbatively stable two-dimensional string backgrounds and their dual matrix models allows the study of complete scattering matrices in string theory. In this note we adapt work of Moore, Plesser, and Ramgoolam on the bosonic string to compute the exact S-matrices of 0A and 0B string theory in two dimensions. Unitarity of the 0B theory requires the inclusion of massless soliton sectors carrying RR scalar charge as asymptotic states. We propose a regularization of IR divergences and find transition probabilities that distinguish the otherwise energetically degenerate soliton sectors. Unstable D-branes can decay into distinct soliton sectors.